Eleven new species of Athacryvac Braet & van Achterberg from the Neotropical Region (Hymenoptera, Braconidae, Rogadinae) - Shimbori, Eduardo Mitio; Shaw, Scott Richard; Almeida, Luis Felipe Ventura De (Zootaxa, 2016)
The neotropical genus Athacryvac Braet & van Achterberg was recently described based on two species from French Guiana. Despite the resemblance of these species with the diverse and widespread genus Aleiodes, the authors opted to erect the new genus based on several synapomorphies. With the analysis of more comprehensive morphological and geographical variation we propose reclassifying Athacryvac as a subgenus within Aleiodes. In this paper we describe 11 new neotropical species of the subgenus Athacryvac: Aleiodes (Athacryvac) achterbergi Shimbori & Penteado-Dias sp. nov., Aleiodes (Athacryvac) amazoniensis Shimbori & Almeida sp. nov., Aleiodes (Athacryvac) braeti Shimbori & Shaw sp. nov., Aleiodes (Athacryvac) choco Shimbori sp. nov., Aleiodes (Athacryvac) donaldquickei Shimbori & Penteado-Dias sp. nov., Aleiodes (Athacryvac) gonzalezi Shimbori & Shaw sp. nov., Aleiodes (Athacryvac) paradoxus Shimbori & Penteado-Dias sp. nov., Aleiodes (Athacryvac) soaresi Shimbori & Penteado-Dias sp. nov., Aleiodes (Athacryvac) tico Shimbori & Shaw sp. nov., Aleiodes (Athacryvac) torresi Shimbori & Shaw sp. nov., Aleiodes (Athacryvac) zaldivari Shimbori & Almeida sp. nov. We also provide new morphological and distributional data for the previously described A. alternatus and A. fuscatus, as well as the description of the male of the later species. The 13 known species of Aleiodes (Athacryvac) stat. nov. are restricted to the Neotropical Region, ranging from southern Mexico to southern Brazil. With our current results, there are 104 described neotropical Aleiodes species.